Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1001/jamanetworkopen.2021.34274
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Stillbirth Among Pregnant People With Sickle Cell Trait

Abstract: Key Points Question Is sickle cell trait associated with an increased risk of stillbirth? Findings In this cohort study of 50 560 patients and 63 334 deliveries (including 2482 deliveries from patients with sickle cell trait and 215 deliveries from patients with sickle cell disease) both sickle cell trait and sickle cell disease were associated with increased risk of stillbirth after adjusting for known risk factors. Meaning This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 56 publications
1
6
0
Order By: Relevance
“…The most noticeable finding in this study is the 15-fold increase in the risk of IUFD among women with SCT (3%) compared to women with normal hemoglobin (0.2%) (P<0.0001). Similar results were reported by Canelon et al's study [19]. This might be attributed to the sickling of maternal blood red cells at the placental blood vessels which may lead to decreased oxygenation, thrombosis, and placental infarctions causing intrauterine fetal hypoxia [20].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The most noticeable finding in this study is the 15-fold increase in the risk of IUFD among women with SCT (3%) compared to women with normal hemoglobin (0.2%) (P<0.0001). Similar results were reported by Canelon et al's study [19]. This might be attributed to the sickling of maternal blood red cells at the placental blood vessels which may lead to decreased oxygenation, thrombosis, and placental infarctions causing intrauterine fetal hypoxia [20].…”
Section: Discussionsupporting
confidence: 76%
“…In this retrospective study, SCT occurred in approximately 16.4% of all patients delivered in SMC during the study period. The incidence is considered relatively high in comparison to other studies which reported a lower incidence of SCT patients [8,19]. Canelon et al [19] and Larrabee et al [8] reported that the incidence of SCT among parturition mothers is 3.9% in Pennsylvania and 10.2% among African American women, respectively.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…It was, for example, the only country in which HIV 2 was more widespread than HIV 1 in the past decades ( 23 ); and multidrug resistant uberculosis (TB) has lower incidence than in other West-African countries ( 24 ). Furthermore, the very high maternal and infant mortality rates of Guinea Bissau (child mortality rates are the highest worldwide at 152.5 per 1,000 livebirths) ( 25 ), as well as the increased risk of stillbirth in SA carriers ( 26 ), could justify a higher number of children with SS dying earlier and not being diagnosed. Also, there is a lower rate of HbSA children being born from S carrier mothers.…”
Section: Discussionmentioning
confidence: 99%
“…13 Pregnancy is a stressful physiological event, often associated with emotional changes, anxiety, and depression. [14][15] Impact of SCT on pregnancy outcome has been equivocal, with some studies have reported adverse outcomes, [16][17][18][19][20][21][22][23][24][25][26][27] and contraception has been suggested, 28 whereas others have not, [29][30] also in consideration of greater resistance of carriers to malaria in pregnancy 29. The reasons for the contradictory findings are not clear. However, factors such as nutritional status before and during pregnancy may play a significant role.…”
mentioning
confidence: 99%